Biobanks: Experience of the School of Medicine and the “Dr. José Eleuterio González” University Hospital of the Universidad Autónoma de Nuevo León - Maria Lourdes Garza-Rodríguez; JORGE ANGEL ISIDRO ASCACIO MARTINEZ; ANTONIO ALI PEREZ MAYA; DIANA CRISTINA PEREZ IBAVE; DANIELA ESTEFANIA MONSIVAIS OVALLE (UANL. Facultad de Medicina, 2014)
Medical research has greatly beneited from molecular biology and increasingly relies on tools from the “omics” disciplines (mainly genomics, transcriptomics, proteomics and metabolomics). The availability of biological samples preserved with high quality standards is a sine qua non condition for such studies and their repositories are referred to as biobanks. Biobanks support the transportation, storage, preservation, and initial pathological and analytical examinations of biospecimens, as well as the protection of relevant information and the comparison of clinical and laboratory findings. A biobank facility is one of the most valuable tools the academic medicine organizations can offer to their researchers to improve the competitiveness of their current and future medical research. it acts as an essential bridge and an effective catalyst for research synergies between basic and clinical sciences, and it can be potentiated with efforts to raise funds for acquiring and maintaining cutting-edge analytical infrastructure to better serve its clinical, pharmaceutical and biotech clients.